Anti‐microbial peptide gene expression during oral vaccination: analysis of a randomized controlled trial. (29th August 2016) - Simuyandi, M.; Kapulu, M.; Kelly, P.
Summary: We have observed previously that micronutrient supplementation ameliorated suppression of α‐defensin expression during diarrhoea. However, how interactions between anti‐microbial peptide (AMP) expression and diarrhoeal disease are altered by micronutrient supplementation remain unclear. Using oral vaccination as a model of intestinal infection, we measured changes in AMP expression during multiple micronutrient supplementation. In the first part, volunteers underwent duodenal jejunal biopsy before and at 1, 2, 4 or 7 days after administration of one of three live, attenuated oral vaccines against rotavirus, typhoid and enterotoxigenic Escherichia coli . In the second part, participants were randomized to receive a multiple micronutrient supplement or placebo for 6 weeks before undergoing intestinal biopsy, vaccination against typhoid and rebiopsy after 14 days. Expression of human alpha‐defensin (HD)5, HD6, hBD1, hBD2 and LL‐37 was measured by quantitative reverse transcription–polymerase chain reaction. Taken together, the bacterial vaccines, but not rotavirus vaccine, reduced HD5 expression ( P = 0·02, signed‐rank test) and reduced LL‐37 expression in seven of the eight individuals whose biopsies had expression prevaccination ( P = 0·03). hBD2 was not detected. In the controlled trial, HD5 and HD6 expression after vaccination was lower [median ratio 0·5, interquartile range (IQR) = 0·07–2·2 and 0·58, IQR = 0·13–2·3, respectively] than before vaccination. There was no significant effect detected of micronutrient supplementation on expression of HD5, HD6, hBD1 or LL‐37. We conclude that live attenuated bacterial vaccines, but not rotavirus vaccine, can reduce intestinal α‐defensins, and typhoid vaccine reduced LL‐37 expression. We found no evidence that micronutrient supplementation in the short term had any impact on anti‐microbial peptide expression. Abstract : Typhoid and ETEC vaccines suppress human defensin 5 gene expression in African volunteers, but rotavirus vaccine does not.